THE EFFECT OF MICRO INFLUENCERS AND CUSTOMER ENGAGEMENT ON PURCHASE INTENTION OF MILLENNIALS AND GEN Z WITH FOMO AS A MODERATING VARIABLE (A STUDY ON N'PURE PRODUCTS IN TIKTOK SHOP) - Ni Kadek Mei Diana; Ponirin; Syamsul Bahri Dg. Paranai; Anisah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The development of social media especially TikTok, has change marketing strategy with present micro influencer as source more information​ credible and close with consumers , especially in the younger generation young . On the other hand , the phenomenon Fear of Missing Out (FOMO) is increasing push consumer For follow trend beauty and make decision more purchases​ fast . Based on condition said , research This aim For analyze influence Micro Influencers and Customer Engagement to Purchase Intention on product N'Pure on TikTok Shop, as well as test the role of FOMO as variables moderation . Research use approach quantitative with involving 125 respondents users active TikTok ever see content promotion N'Pure . Data analysis was performed use PLS-SEM technique through SmartPLS . Research results show that Micro Influencers, Customer Engagement , and FOMO are influential positive and significant to Purchase Intention . In addition , FOMO has an influence positive to Customer Engagement as well as strengthen connection between Micro Influencers and Customer Engagement . However , FOMO actually weaken connection Customer Engagement to Purchase Intention . In general overall , findings This show that behavior consumers on TikTok are influenced by a combination of factor social , digital engagement , and conditions psychological FOMO, so that give implications important for brand in designing marketing strategies based more influencers​ effective .